Design of a PI-Controller Based on Time-Domain Specification Utilizing the Parameter Space Approach. Issue 2 (2020) - Popp, Eduard; Tantau, Mathias; Wielitzka, Mark; Giebert, Dennis; Ortmaier, Tobias
Abstract: In automotive application PI and PID controllers are widely used. Commonly the controller parametrization is performed in a heuristic manner in the vehicle at different operating points. Model-based approaches offer many advantages like a reduced effort of the design process and a more systematically investigation of the parameter set. Circumventing experiments at the vehicle is not feasible, however the goal is to achieve a significant reduction of this part of work. The aim of this paper is to find the controller parameter region, that ensures compliance with defined measures of the controller performance in time domain. On the basis of the parameter space approach these measures need to be transferred into the s-domain, which is shown exemplary for a second order system and a PI-controlled integrator system. The latter serves as a simple vehicle drive train model for the design of the engine idle speed controller.